Redress for academic success: possible ‘lessons’ for university support programmes from a high school literacy and learning intervention - Osman, Ruksana; Andrews, Douglas (South African Journal of Higher Education, 2016)
This paper aims to contribute to ongoing research and debate in the area of under-preparedness of university students, with particular reference to the literacy skills and cognitive strategies needed to cope with the demands of academic studies. After a review of literature in the field we present findings from a case study of a cognitive learning and academic literacy support programme offered to secondary school learners and argue that this programme could also be of value to underprepared university students. The programme was named the Integrated Approach to Literacy Instruction (IATLI) and was used with a purposively selected group of learners who were struggling with their studies. We argue that a mediated learning support programme offered to secondary school learners that address both literacy and cognitive learning strategies could be of value to underprepared university students.